Pengaruh Kualitas Website www.pajak.go.id Terhadap Citra Direktorat Jendral Pajak (Survei pada Kantor Pelayanan Pajak Tangerang Timur) - Romadoni, Suci; Hardiyanti, Rini; Yoman, Mad (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This research is entitled "The Influence of Website Quality www.pajak.go.id on the Image of the Directorate General of Taxes (Survey at the East Tangerang Tax Service Office)". This research aims to find out what influence the quality of the website www.pajak.go.id has on the image of the Directorate General of Taxes at East Tangerang Tax Service Office.This research uses Stimulus-Response Theory, the basic assumption of this theory is that certain verbal words, nonverbal signals, techniques and symbols will cause other people to respond in a certain way. The paradigm used in this research is the positivism paradigm with descriptive quantitative research methods. Researchers used data collection techniques through questionnaires with the SPSS measuring tool. The population used in this research were taxpayers within the East Tangerang Tax Service Office, totaling 114,311 with a sample of 100 respondents. The results of this research show that there is a positive and significant influence of the website quality variabel on image as shown by the results of the coefficient of determination analysis test which shows that the R Square Value is 0.199 or if converted into a percent, it is 19.9%, which means it can be concluded that there is an influence on the quality of the website www .pajak.go.id on the image of the Directorate General of Taxes in the East Tangerang Tax Service Office.